Assessment of the Di?erent Modalities of Treatment in Paediatric Cerebral Palsy Patients - Gaurang Dilip Kumar Pabani; Mehta, Rajeshri Rajendra; Shah, Pramod Chandulal (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: To assess the effects of injection of citicoline in combination with physiotherapy versus physiotherapy alone, to advance the functional outcome in paediatric patients with cerebral palsy. Subjects & Methods: A total of 150 paediatric patients diagnosed with cerebral palsy were incorporated into the study. The average age of the patient included in the study was found to be 36 months. All the patients enrolled in the study were referred to the paediatric neurological department. Results: The mean age of the patient was 36 10 months. Out of the 150 total patients, 60% were boys and 40% were girls. When the percentage of improvement was compared between the groups, the study group was established to be statistically significant. (P = 0.02). Conclusion: Citicoline is efficient and secure in the treatment of gross motor function combination with physiotherapy in patients with cerebral palsy. Physical therapy is frequently the first move in managing cerebral palsy.